Hantavirus and criminality: disease and family - Trettel, Ana Cláudia Pereira Terças; Graça, Bianca Carvalho da; Nascimento, Vagner Ferreira do; Hattori, Thalise Yuri; Santos, Rogerio Alexandre Nunes dos; Menezes, Andreza Lucia de; Via, Alba Valéria Gomes de Melo; Silva, Juliana Herrero da (Revista de Epidemiologia e Controle de Infecção, 2020)
Background and objectives: Hantavirus is a pathogen that causes a viral disease with anacute and severe presentation, and a high mortality rate. In face of a sudden loss, somefamilies may not conceive the complete absence of the deceased relative. Thus, we sought tounderstand the changes that took place in a family after the death of the provider byHantavirus Pulmonary Syndrome (HPS). Methods: A descriptive exploratory study with aqualitative approach of the type case report. Data collection took place between October andDecember 2016 through recorded individual interviews and using questions about familydynamics after family provider’s death of HPS, which were assessed by content analysis inthe light of Roy's theory. Results: It was observed that the illness and death of the familypatriarch weakened the family's strengths and resources, leading to a period of mourning anddespair. In addition, unemployment among other family members worsened socioeconomicconditions, seeing drugs as an alternative for support as it became a commercial activity, andthe rise of a command in the region that culminated in the arrest of the wife, two daughtersand a son of the deceased. Conclusions: In this case, it was evidenced that the family wasweakened due to the illness and death of their loved one by HPS, and because of the lack ofsupport and welcome from the reference social services, they chose to act in criminality and itended up with the arrest of four members.